Pendrin localizes to the adrenal medulla and modulates catecholamine release - Lazo-Fernandez, Yoskaly (Am J Physiol Endocrinol Metab, 2015)
Pendrin (Slc26a4) is a Cl(−)/HCO(3)(−) exchanger expressed in renal intercalated cells and mediates renal Cl(−) absorption. With pendrin gene ablation, blood pressure and vascular volume fall, which increases plasma renin concentration. However, serum aldosterone does not significantly increase in pendrin-null mice, suggesting that pendrin regulates adrenal zona glomerulosa aldosterone production. Therefore, we examined pendrin expression in the adrenal gland using PCR, immunoblots, and immunohistochemistry. Pendrin protein was detected in adrenal lysates from wild-type but not pendrin-null mice. However, immunohistochemistry and qPCR of microdissected adrenal zones showed that pendrin was expressed in the adrenal medulla, rather than in cortex. Within the adrenal medulla, pendrin localizes to both epinephrine- and norepinephrine-producing chromaffin cells. Therefore, we examined plasma catecholamine concentration and blood pressure in wild-type and pendrin-null mice under basal conditions and then after 5 and 20 min of immobilization stress. Under basal conditions, blood pressure was lower in the mutant than in the wild-type mice, although epinephrine and norepinephrine concentrations were similar. Catecholamine concentration and blood pressure increased markedly in both groups with stress. With 20 min of immobilization stress, epinephrine and norepinephrine concentrations increased more in pendrin-null than in wild-type mice, although stress produced a similar increase in blood pressure in both groups. We conclude that pendrin is expressed in the adrenal medulla, where it blunts stress-induced catecholamine release.